Blockchain technology: challenges and opportunities for banks. (16th January 2020) - Martino, Pierluigi
This paper explores blockchain technology's potential implications for banks. This study is based on qualitative-based interviews with three professional bankers in different European banks that are dealing with the challenges of blockchain. The results indicate that blockchain technology is both a threat to and an opportunity for banks, providing support to the argument that blockchain is a disruptive technology that will create new opportunities for banks and new risks to their business. Nonetheless, the current lack of regulation and some technical limitations of the technology mean that blockchain is an opportunity for rather than a risk to banks. Blockchain technology may vastly improve banking processes' efficiency and therefore the products and services banks offer customers, particularly in areas such as lending, payments and capital markets.